Solitary Fibrous Tumor in the Round Ligament of the Liver: A Fortunate Intraoperative Discovery - Beyer, Laura (S. Karger AG, 2012)
Solitary fibrous tumors (SFTs) are mesenchymal neoplasms of fibroblastic origin, most commonly found in the pleura. Numerous extrathoracic locations have been reported during the last 2 decades. Herein, we report the first case of an SFT in the round ligament of the liver. A 46-year-old Caucasian man presented with a 12-month history of abdominal pain. An ultrasonography-guided microbiopsy first revealed a desmoid tumor. After failure of first- and second-line medical treatments (celecoxib and tamoxifen, then imatinib), histological reexamination was suspicious for a low-grade sarcoma. MRI was also suspicious for a malignant process. Hence, surgery was decided. Laparotomy found a huge and well-limited tumor that, unexpectedly, was appended to the round ligament of the liver and free from any other intra-abdominal contact. The tumor was easily removed. Excision was monobloc and macroscopically complete. Histological analysis diagnosed an SFT arising from the round ligament of the liver. No adjuvant treatment was given. Ten months after surgery, the patient is alive without any signs or symptoms of relapse. This is the first report of SFT arising from the round ligament of the liver. It illustrates the difficulty in diagnosing such tumors. Whilst diagnosis of SFT is rare, it should be kept in mind to allow early diagnosis and complete surgical resection, which provide the best chance for recovery.